2009
DOI: 10.1086/600385
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of Microbial and Inflammatory Events Immediately PrecedingEscherichia coliRecurrent Urinary Tract Infection in Women

Abstract: Background A prospective cohort study was conducted to characterize the temporal sequence of microbial and inflammatory events immediately preceding Escherichia coli recurrent urinary tract infection (rUTI). Methods Women with acute cystitis and a history of UTI within the previous year self-collected periurethral and urine samples daily and recorded measurements of urine leukocyte esterase, symptoms, and sexual intercourse daily for 3 months. rUTI strains were characterized by pulsed-field gel electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 41 publications
4
98
0
Order By: Relevance
“…In several studies that shown whether particularly the fecal flora members are UTI factor or not (9,10). Uropathogenic E. coli isolates are located phylogenetically in group B2 and less frequently in the group D. However non-pathogen E. coli isolates are often in group A and B1 and often have less virulence factors.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies that shown whether particularly the fecal flora members are UTI factor or not (9,10). Uropathogenic E. coli isolates are located phylogenetically in group B2 and less frequently in the group D. However non-pathogen E. coli isolates are often in group A and B1 and often have less virulence factors.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains were routinely cultured in Luria-Bertani broth without antibiotics. Isolates were derived from four sources: (1) well-characterized, published representative pathogenic and commensal strains (n59); (2) isolates collected in previously published clinical studies in Seattle, representing various clinical syndromes of urinary tract infection (n5155) (Czaja et al, 2009;Garofalo et al, 2007;Hooton et al, 1996;Johnson et al, 1987Johnson et al, , 1988Johnson et al, , 1991 as well as control faecal-commensal isolates (n520) (Stapleton et al, 1991); (3) strains from the E. coli reference (ECOR) collection (n568) (Ochman & Selander, 1984) and (4) clinical enterohaemorrhagic E. coli (EHEC) isolates (n57).…”
Section: Methodsmentioning
confidence: 99%
“…The study population for all studies was non-pregnant, outpatient women ages 18 to 49 seen in the Hall Health Primary Care Center (student health clinic) at the University of Washington (Czaja et al, 2009;Garofalo et al, 2007;Hooton et al, 1996) or Group Health Cooperative of Puget Sound (Garofalo et al, 2007;Hooton et al, 1996), except for isolates collected from in-patients hospitalized with pyelonephritis and/or urosepsis. Pyelonephritis isolates were collected from 20 women ages 18 to 45 hospitalized in one of four hospitals in Seattle (Johnson et al, 1991) and 2 were out-patients (Garofalo et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors also increase a woman's likelihood of infection, including sexual activity, oral contraceptives, oestrogen deficiency, diabetes, obstructing lesions and genetic factors such as blood group secretor status (Harrington & Hooton, 2000;Scholes et al, 2000). Among the causative agents of UTI, Escherichia coli is responsible for .90 % of cases and is almost always found amongst the faecal flora of the same host, although these bacteria may be harboured in the vagina or periurethra (Czaja et al, 2009;Moreno et al, 2008).…”
Section: Introductionmentioning
confidence: 99%